Metodologia de infecção experimental e grau de susceptibilidade do híbrido tambacu e Leporinus macrocephalus Garavello & Britski (Osteichthyes, Anostomidae) a quatro inóculos de trofozoítos de Icthyophthirius multifiliis Fouquet (Protozoa, Ciliophora) - Souza, Valéria Nogueira de [UNESP]; Martins, Maurício Laterça [UNESP]; Moraes, Flávio Ruas de [UNESP]; Kronka, Sérgio do Nascimento [UNESP] (Sociedade Brasileira de Zoologia, 2001)
Tropical fishes like Leporinus macrocephalus Garavello & Britski, 1988 (piauçu) and the hybrid tambacu (Piaractus mesopotamicus Holmberg, 1887 pacu male x Colossoma macropomum Cuvier, 1818 tambaqui female) were experimentally infected with four inocula of trophonts of Ichthyophthirius multifiliis Fouquet, 1876 (Protozoa, Ciliophora) and the infection level was evaluated. Each one of twelve experimental units consisted of a tank with 200 liters of water and two specimens of each kind of fish. The following treatments were designed to each tank, in triplicate: 8, 16,32 and 64 trophonts. After 8 days of exposure the fishes were killed and the number of trophonts was counted at a stereoscopic microscope. This assay showed to be feasible at tropical conditions and was able to show that tambacu was more susceptiblc than piauçu.
Methodology of experimental infection and the susceptibility degree of the tambacu hybrid and Leporinus mucrocephalus Garavello & Britski to four inocula of trophonts of Ichtyophthirius multifiliis Fouquet
Keywords: Ichthyophthirius multifiliis; tropical fish; experimental infection; susceptibility